2020
DOI: 10.20377/jfr-371
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ nonstandard work schedules and children’s social and emotional wellbeing: A mixed-methods analysis in Germany

Abstract: Many children live in households where either one or both parents work nonstandard schedules in the evening, night or weekend. Using a mixed methods design, this study examined whether nonstandard work schedules were linked to lower social and emotional wellbeing in children. The quantitative analysis based on the German Family Panel Study (pairfam) showed that children whose parents worked rotating shifts and other types of nonstandard schedules reported elevated levels of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The discovered gender differences in children's reactions to the risk factors in our study are supported by some previous research (Claessens & Chen, 2013; Li et al, 2020; Morrisey, 2009). Scholars have emphasised a child's gender as an important moderating factor (Winer & Phillips, 2012) that ought to be considered when investigating children's well‐being in the context of parental NSWS (Li et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The discovered gender differences in children's reactions to the risk factors in our study are supported by some previous research (Claessens & Chen, 2013; Li et al, 2020; Morrisey, 2009). Scholars have emphasised a child's gender as an important moderating factor (Winer & Phillips, 2012) that ought to be considered when investigating children's well‐being in the context of parental NSWS (Li et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Based on previous research (Claessens & Chen, 2013; Li et al, 2014), we hypothesised that the associations between various family‐ and work‐related risk factors would affect boys' and girls' social–emotional well‐being in flexible scheduled ECEC differently. However, we did not make more specific gender‐related expectations concerning the work and care arrangement effects on boys and girls due to contradictory findings in previous research (Li et al, 2020; Morrisey, 2009; Rönkä, Malinen, Metsäpelto, et al, 2017).…”
Section: Research Questions and Hypothesesmentioning
confidence: 80%
See 1 more Smart Citation
“…Despite consistent evidence for negative effects of parents' nonstandard work schedules on young children (Grzywacz et al, 2016;Han, 2020;Kaiser et al, 2019;Li et al, 2014;Li et al, 2020), relatively few studies have examined the association between such work schedules and adolescent mental health (Dockery et al, 2009;Dockery et al, 2016;Han et al, 2010;Han & Miller, 2009). This is despite the fact that adolescents are at greater risk of anxiety and depression than young children (Andersen & Teicher, 2008), have a high incidence of suicide (Andersen & Teicher, 2008) and engage in more risk-taking behaviour (e.g., excessive alcohol consumption and substance use) (Squeglia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Non‐standard work schedules can be asynchronous with the institutional rhythm of ECEC services, with leisure and community activities, with the individual rhythms of other family members and with family rhythms, such as the timings of family meals or other activities. Some studies have found that parents' non‐standard work schedules can make family environments chaotic because of the difficulties of planning everyday life (Li et al, 2020). Aho (2019) used the concept of ‘rhythm conflicts’ when describing the unsynchronised social rhythms that truck drivers face in their work and personal lives, including their family members' rhythms and the rhythms of other social and leisure activities.…”
Section: Introductionmentioning
confidence: 99%